2007
DOI: 10.1175/jas3945.1
|View full text |Cite
|
Sign up to set email alerts
|

Convectively Coupled Kelvin Waves in an Idealized Moist General Circulation Model

Abstract: The dynamics of convectively coupled Kelvin waves and their dependence on convection scheme parameters are studied within a simplified moist general circulation model. The model consists of the primitive equations on the sphere over zonally symmetric aquaplanet, slab mixed layer ocean boundary conditions, and idealized physical parameterizations including gray radiative transfer and a simplified Betts-Miller convection scheme. This framework allows the authors to study the dependence of Kelvin waves on quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 53 publications
8
61
0
Order By: Relevance
“…For example, NZC07 found that convection was strongly organized by a single, robust convectively coupled Kelvin wave (CCKW). That convection is organized into a dominant, domain-length CCKW was also found for a global aquaplanet simulation by Frierson (2007). In our case, it will be shown that this wave is not so dominant when the free-slip wall at the equator is removed and that an equatorial wave feature similar to the mixed Rossbygravity wave will appear.…”
Section: B Current Issues and Open Questionssupporting
confidence: 77%
See 1 more Smart Citation
“…For example, NZC07 found that convection was strongly organized by a single, robust convectively coupled Kelvin wave (CCKW). That convection is organized into a dominant, domain-length CCKW was also found for a global aquaplanet simulation by Frierson (2007). In our case, it will be shown that this wave is not so dominant when the free-slip wall at the equator is removed and that an equatorial wave feature similar to the mixed Rossbygravity wave will appear.…”
Section: B Current Issues and Open Questionssupporting
confidence: 77%
“…For HYP2.5-8N and IEP, the eddy fluxes are mostly associated with the TCs; for HYP2.5, the eddy fluxes are maximized only a few degrees on either side of the equator and are associated with the meridional circulations generated by the CCKWs. Although pure Kelvin waves have zero meridional flow, CCKWs in the atmosphere (Wheeler et al 2000), in idealized simulations (NZC07; Frierson 2007), and in the theory of Dias and Pauluis (2009) are found to have significant meridional flow into and out of their convecting regions.…”
Section: A Understanding the Midlevel Inflowmentioning
confidence: 94%
“…Dor15 is only able to improve on this issue by strongly reducing rw c . By increasing the relaxation time scale of the relaxation closure in CTRL, similar changes are to be expected (Frierson 2007). For Dor15, it seems that changing the mean M b has a larger impact on the representation of the equatorial waves than changing the magnitude of stochastic fluctuations of M b on a time step level.…”
Section: Discussionsupporting
confidence: 59%
“…Equation (3) can be separated into horizontal and vertical components as Previous research has used G y in various ways such as a diagnostic quantity in general circulation models (e.g., Frierson 2007;Hannah andMaloney 2011, 2014;Benedict et al 2014), in observational data (e.g., Yu et al 1998;Sobel et al 2014), 2 as an output quantity of a MJO toy model (e.g., Raymond and Fuchs 2009), and as an input parameter of a MJO toy model (e.g., Sugiyama 2009;Maloney 2012, 2013). As Hannah and Maloney (2011) and Masunaga and L'Ecuyer (2014) pointed out, values of G y generally fluctuate in convective life cycles primarily as a result of variations of vertical velocity profiles (as seen in Fig.…”
Section: A Gms With Different Frequenciesmentioning
confidence: 99%